2020
DOI: 10.1007/s12265-020-10049-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of the NLRP3 Inflammasome in Atherosclerosis, Coronary Artery Disease, and Acute Myocardial Infarction

Abstract: Cardiovascular disease (CVD) remains the leading cause of mortality and morbidity worldwide. Atherosclerosis is responsible for the majority of cardiovascular disorders with inflammation as one of its driving processes. The nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome, responsible for the release of the pro-inflammatory cytokines, interleukin-1β (IL-1β), and interleukin-18 (IL-18), has been studied extensively and showed to play a pivotal role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 82 publications
1
51
0
1
Order By: Relevance
“…Due to the intimate relationship between the two organ systems, the concept of the cardiorenal syndrome has been developed [ 1 ]. As inflammation is one of the major drivers for most heart diseases [ 2 , 3 , 4 ], it is interesting to note that most renal diseases are also associated with inflammation [ 5 , 6 , 7 ]. Moreover, in early stages of renal dysfunction, when the glomerular function is still intact, systemic and local inflammation leads to downregulation of molecules that have renal protective effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the intimate relationship between the two organ systems, the concept of the cardiorenal syndrome has been developed [ 1 ]. As inflammation is one of the major drivers for most heart diseases [ 2 , 3 , 4 ], it is interesting to note that most renal diseases are also associated with inflammation [ 5 , 6 , 7 ]. Moreover, in early stages of renal dysfunction, when the glomerular function is still intact, systemic and local inflammation leads to downregulation of molecules that have renal protective effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moderate regulation of the inflammatory response after MI is very important to prevent HF; however, an excessive inflammatory response will lead to the deterioration of myocardial remodeling and dysfunction after MI. Many studies have found that NLRP3 is activated after MI, resulting in an enhanced inflammatory response and cardiac dysfunction [ 26 ]. To determine whether the effect of LQF and perindopril on improving cardiac function is related to the inflammasome, we studied the expression of NLRP3 inflammasome in the heart.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers concluded that NLRP3 protein might not play a role in the acute development of MI due to low cardiac expression (84), which may explain the failure of colchicine to take positive results in patients with ACS. However, more evidence has proven that NLRP3 inflammasomemediated inflammation does have an important role in ACSs (77,85). On the other hand, studies have also shown that colchicine does not necessarily activate NLRP3 (86).…”
Section: Anti-inflammatory Effects Of Colchicine In Atherosclerotic Heart Disease Need Further Evaluationmentioning
confidence: 99%